Gallium Nitride (Gan) Based Gas Sensor Using Catalytic Metal - Hudeish, Abdo Yahya Omer (2005)
In this work, Pt, Pd, Ag and Ni were deposited on p type and n type of GaN and AIGaN as catalytic metals contact using sputtering system through meta! mask to detect N2, H2 and CH4 gases with different concentrations and different metal thicknesses with a range of SO-300nm. Samples were annealed at various temperatures from 500°C up to 1000°C for 5 min in argon prior to sensing charactersation. Special chamber was designed and built to test the sensor capability. All samples were examined by electrical characterization, using current-voltage (I-V) with temperature range from 25°C to 500°C. All samples were found capable of detecting gas at a broad temperature range from 25°C to 500°C. The resistance of samples was measured with different parameters such as thickness, annealing temperatures, gases, and concentration of gases and operated temperatures. All resistance of the samples, time response and recovery time were measured at different temperature range (25°C- 500°C). The annealing temperature plays an important role in the changes of sensitivity due to changes of parameter such as distance between grains, outdiffusion or indiffusion of metals, and formation of dipoles. The change in current increases with measurement temperature and begins immediately upon introduction of the hydrogen. Pt/n-AIGaN showed a good device selectivity and high sensitivity as hydrogen gas sensor compared to Pt/p-GaN and PUn-GaN respectively.